A post-American world? Assessing the cognitive and attitudinal impacts of challenges to American exceptionalism. Issue 1 (2nd January 2018) - Gilmore, Jason; Rowling, Charles
ABSTRACT: A number of voices have emerged in U.S. political discourse questioning the legitimacy of American exceptionalism, suggesting we are in a "post-American world." Our research examines the effects that political messages that explicitly challenge American exceptionalism can have on U.S. public opinion. Drawing upon social identity theory, we find that explicit challenges to American exceptionalism significantly impact Americans' views toward their own nation, their willingness to denigrate foreign publics, and their broader foreign policy preferences.